PENGGUNAAN KULIT BATANG JAMBLANG (Syzygiumcumini) DALAM FORMULASI PEWARNA RAMBUT - Karnerius Harefa; Artha Yuliana Sianipar; Siti Nurbaya; Sisca Mayryanisa (Jurnal Farmanesia, 2017)
Hair dye is a cosmetic used in hair makeup to color hair, either to restore the original hair color or change the original hair color to a new color. Jamblang bark contains dyes and produces tannins which are used to dye textiles. The purpose of this study was to determine that Jamblang bark extract could be formulated as a hair dye. Hair dye preparations contain Jamblang bark extract with concentrations of A (2.5%), B (5%), C (7.5%), and D (10%). Observation of color stability was carried out by means of a stability test against 15 washes and exposure in the sun for 5 hours on colored hair, then an irritation test was carried out. This study shows that a formula made with Jamblang bark extract can give hair a brown color. The longer the immersion of gray hair in hair dye preparations, the darker the resulting brown color at a concentration of C (7.5%). The results of stability tests against washing and sunlight showed that there was no change in hair color and did not cause skin irritation. Jamblang bark extract can be formulated as hair dye. The best dye was obtained from Formula C which consisted of 7.5% Jamblang stem bark extract producing a dark brown color.